Mind the gap: unemployment in the new EU regions - Anna Maria Ferragina; Francesco Pastore (Institute for the Study of Labor (IZA), 2005)
The paper surveys the theoretical and empirical literature on regional unemployment during transition in Central and Eastern Europe. The focus is on Optimal Speed of Transition (OST) models and on comparison of them with the neoclassical tradition. In the typical neoclassical models, spatial differences essentially arise as a consequence of supply side constraints and institutional rigidities. Slow-growth, high-unemployment regions are those with backward economic structures and constraints on factors mobility contribute to making differences persistent. However, such explanations leave the question unanswered of how unemployment differences arise in the first place. Economic transition provides an excellent testing ground to answer this question. Prefiguring an empirical law, the OST literature finds that the high degree of labour turnover of high unemployment regions is associated with a high rate of industrial restructuring and, consequently, that low unemployment may be achieved by implementing transition more gradually. Moreover, international trade, FDI and various agglomeration factors help explain the success of capital cities compared to peripheral towns and rural areas in achieving low unemployment.
Keywords: J6; P2; R1; R23; 330; regional unemployment; structural change; labour turnover; optimal speed of transition; Central and Eastern Europe; Regionale Arbeitslosigkeit; EU-Staaten (Osteuropa)